The Europeanisation of social policies in Portugal - Silva, Pedro Adão e (Portuguese Journal of Social Science, 2011)
This article analyses how three different instruments of European social policy have been implemented in Portugal. I claim that the reasons for compliance rest in the combination of a favourable context created by a strong European legacy in domestic policies, with the convergence between the European pressure and the domestic policy agenda in policy arenas, whose characteristics facilitate policy change. I make the case that there is no dualism between a politicisation and a socialisation approach to the Europeanisation of domestic public polices. When compliance occurs, both mechanisms are present. Responses to European pressures reflect both the introduction of new incentive structures and the creation of new patterns of social relations. This is particularly true for European social policies. Those resources have a delayed effect by formatting policy arenas and giving meaning to certain incentives and providing a social context in which pressures are perceived to be cost-effective and legitimate. There is no relation between a priori convergence capacity of European policy instruments and their de facto effectiveness ? the distinctive traits of each is central to understand the extent to which EU policy initiatives mobilise domestic coalitions, which prove decisive for the resistance of policy innovation.